Regular nanofabrics in emerging technologies design and fabrication methods for nanoscale digital circuits - Ben Jamaa, M. Haykel; SpringerLink (Online service). (Dordrecht Springer Netherlands Imprint: Springer, 2011)
Regular Nanofabrics in Emerging Technologies gives a deep insight into both fabrication and design aspects of emerging semiconductor technologies, that represent potential candidates for the post-CMOS era. Its approach is unique, across different fields, and it offers a synergetic view for a public of different communities ranging from technologists, to circuit designers, and computer scientists. The book presents two technologies as potential candidates for future semiconductor devices and systems and it shows how fabrication issues can be addressed at the design level and vice versa. The reader either for academic or research purposes will find novel material that is explained carefully for both experts and non-initiated readers. Regular Nanofabrics in Emerging Technologies is a survey of post-CMOS technologies. It explains processing, circuit and system level design for people with various backgrounds.
Acknowledgments. Contents -- 1 Introduction -- 2 Fabrication of Nanowire Crossbars -- 3 Decoder Logic Design -- 4 Decoder Test -- 5 Logic Design with Ambipolar Devices -- 6 Conclusions and Future Work. List of Acronyms -- List of Symbols.
Electronic reproduction.
Keywords: Nanofibers; Nanoelectronics